Variation in Leaf Morphology of Sago Trees (Metroxylon sagu) in South Borneo Province, Indonesia. - Rahman, Hasan Basri Arif; Bintoro, Mochamad Hasjim; Supijatno, Supijatno (Department of Agronomy and Horticulture, IPB University, 2021)
Natural populations of sago (Metroxylon sagu) in Indonesia show morphological variations in its organs, particularly the leaves. The existing variations resulted in sago type names provided by the locals. The sago plant types include Mahang, Buntal, Salak, Madang and Gandut. Sago leaves are economically important in Indonesia, mainly because they provide a potentially profitable and environment-friendly source of house roofing materials. Determining leaf variation among sago plants would provide information for a better way of choosing which among the current accessions/varieties of sago has the best leaf quality and production. Leaf variations in sago were recorded in shape, size, and color. The aim of this study are a) to compare differences in leaf morphology among sago types obtained from different geographic areas, and b) to determine whether these different sago types correspond to certain sago plant grouping. The qualitative and quantitative analysis showed variations in leaf characteristics of sago trees. Additionally, this study shows that based on leaf variations, the sago of South Borneo Province can be separated into two groups. The first group is Mahang and Gandut, which have long rachis, leaflets and leaves, and largest leaf area. The second group composed of Buntal, Salak and Madang accessions, which have short rachis and leaves, and smallest leaf area. Other results showed that there were characters that contributed significantly to the diversity of sago plants in the study area including spines, white stripe or banding on the rachis and petiole length. In line with our results, Mahang and Gandut accessions are the best accessions to be cultivated in the area, because they have wider leaves which support higher rates of photosynthesis. Further study should be conducted on phylogenetic using DNA sequencing to confirm divisions of the two sago groups.